HiPSC‐derived hepatocytes closely mimic the lipid profile of primary hepatocytes: A future personalised cell model for studying the lipid metabolism of the liver. Issue 4 (26th August 2018) - Kiamehr, Mostafa; Alexanova, Anna; Viiri, Leena E.; Heiskanen, Laura; Vihervaara, Terhi; Kauhanen, Dimple; Ekroos, Kim; Laaksonen, Reijo; Käkelä, Reijo; Aalto‐Setälä, Katriina
Abstract: Hepatocyte‐like cells (HLCs) differentiated from human‐induced pluripotent stem cells offer an alternative platform to primary human hepatocytes (PHHs) for studying the lipid metabolism of the liver. However, despite their great potential, the lipid profile of HLCs has not yet been characterized. Here, we comprehensively studied the lipid profile and fatty acid (FA) metabolism of HLCs and compared them with the current standard hepatocyte models: HepG2 cells and PHHs. We differentiated HLCs by five commonly used methods from three cell lines and thoroughly characterized them by gene and protein expression. HLCs generated by each method were assessed for their functionality and the ability to synthesize, elongate, and desaturate FAs. In addition, lipid and FA profiles of HLCs were investigated by both mass spectrometry and gas chromatography and then compared with the profiles of PHHs and HepG2 cells. HLCs resembled PHHs by expressing hepatic markers: secreting albumin, lipoprotein particles, and urea, and demonstrating similarities in their lipid and FA profile. Unlike HepG2 cells, HLCs contained low levels of lysophospholipids similar to the content of PHHs. Furthermore, HLCs were able to efficiently use the exogenous FAs available in their medium and simultaneously modify simple lipids into more complex ones to fulfill their needs. In addition, we propose that increasing the polyunsaturated FA supply of the culture medium may positively affect the lipid profile and functionality of HLCs. In conclusion, our data showed that HLCs provide a functional and relevant model to investigate human lipid homeostasis at both molecular and cellular levels. Abstract : Hepatocyte‐like cells (HLCs) offer an alternative platform to primary human hepatocytes (PHHs) for studying lipid metabolism of the liver; however, their lipid profile has not yet been characterized. We demonstrate that HLCs resemble PHHs by their functionality and showing similarities in their lipid and fatty acid (FA) profile. Unlike HepG2 cells, HLCs contained low levels of lysophospholipids, similar to the content of PHHs. Here, we propose that HLCs provide a functional and relevant model to investigate human lipid homeostasis at both molecular and cellular levels.